Evaluation of spontaneous retinal venous pulsation in primary open-angle and primary angle-closure glaucoma patients - Sylves Patrick; Chan Hui Tze; Rasdi Abdul Rashid; Liza Sharmini Ahmad Tajudin (2020)
Introduction: Spontaneous retinal venous pulsation (SRVP) is a rhythmic variation in the calibre of one or more retinal veins. The incidence of SRVP was reduced in glaucoma patients. It was also reduced in people with raised intracranial pressure compared to a healthy population.